2013
DOI: 10.1002/macp.201300225
|View full text |Cite
|
Sign up to set email alerts
|

Counter‐Anion Effect on the Properties of Anion‐Conducting Polymer Electrolyte Membranes Prepared by Radiation‐Induced Graft Polymerization

Abstract: Graft‐type anion‐conducting polymer electrolyte membranes (AEMs) are prepared by the radiation‐induced graft polymerization of chloromethylstyrene into poly(ethylene‐co‐tetrafluoroethylene) (ETFE) films and subsequent quaternization with trimethylamine. AEMs in the hydroxide form (AEM‐OH) are prepared by immersing the chloride form (AEM‐Cl) in 1 M potassium hydroxide (KOH) solution, followed by KOH and washing with nitrogen‐saturated water to prevent bicarbonate formation (AEM‐HCO3). The AEM‐OH shows conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(61 citation statements)
references
References 22 publications
2
59
0
Order By: Relevance
“…The yields of the conversion of An‐AEM/OH from the chloride to the hydroxide were 75–87% as determined by titrimetric analysis, as shown in Table . In our previous article, the conversion of BA‐AEM/OH was 88–92%; namely, the IEC of the membrane was approximately 90% on the basis of the expected IEC calculated using a millimolar amount of a quaternary ammonium salt in a unit weight (1 g) of the AEM . However, the IECs of An‐AEM/OH were slightly lower than those of previously reported membranes, although the SEM–EDX clearly did not show a chlorine peak.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…The yields of the conversion of An‐AEM/OH from the chloride to the hydroxide were 75–87% as determined by titrimetric analysis, as shown in Table . In our previous article, the conversion of BA‐AEM/OH was 88–92%; namely, the IEC of the membrane was approximately 90% on the basis of the expected IEC calculated using a millimolar amount of a quaternary ammonium salt in a unit weight (1 g) of the AEM . However, the IECs of An‐AEM/OH were slightly lower than those of previously reported membranes, although the SEM–EDX clearly did not show a chlorine peak.…”
Section: Resultsmentioning
confidence: 74%
“…In the previous article, the basicity of the counter anion of the graft‐type AEMs appeared to strongly affect the conductivity and water uptake . It can be assumed that the large differences in water uptake when different counter anions are used result from the different stabilities of the quaternary ammonium salts of the AEMs.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Walsby et al [201] used this technique to examine the solvent effects of toluene and n-propanol in the grafting of styrene to PVDF. Koshikawa et al [202] used 60 Co g-rays to pre-irradiate ETFE films, which were then treated by chloromethyl styrene and trimethylamine to prepare modified ETFE membranes (AEM-Cl). In their study, the quantitative conversion from Cl À to HCO 3 À forms was confirmed by analysis using energy-dispersive X-ray spectroscopy and SEM (EDX-SEM).…”
Section: Microstructural Studies Using Sem and Afmmentioning
confidence: 99%